Folarin 2 (CD) [sound recording] - Wale, 1984- (Warner Records, 2021)
Wale's most inflective and proactively balanced body of work to date. Core hip-hop fans will relish in the big boy raps in Tiffany Nikes; and Fluctuate while records like More Love show the growth and evolution of Wale as both a father and a man.